Analisis Strategi Marketing Mix Dalam Optimalisasi Bisnis Bucket - Raras Wardah Kartika Wati; Anita Salsabila Putri; Dwi Astuti (CV. ITTC INDONESIA, 2025)
The creative industry is experiencing rapid growth along with the increasing demand for unique and personalized products, one of which is bouquet. Flawra, a business that focuses on creativity and innovation, is here to fulfill consumer needs by providing a wide range of bouquets for events such as graduations, birthdays, and weddings. However, despite having promising market opportunities, Flawra faces various obstacles that hinder the optimal growth of its business. This study aims to analyze Flawra's business feasibility using the 4P marketing mix approach (Product, Price, Promotion, Place). The results of the analysis show that the main obstacles include limited product variety, challenges in procuring raw materials, fluctuations in material prices, lack of promotional activities on social media, and less strategic business locations. To overcome these obstacles, Flawra needs to conduct a comprehensive feasibility study to identify opportunities and threats, while designing a more effective marketing strategy.Through the 4P marketing mix approach, Flawra can increase product innovation, set competitive prices, optimize social media promotions, and find solutions for a more strategic location. With these strategic steps, Flawra is expected to strengthen its competitiveness in a competitive market and achieve more optimal business growth.